Screening and managing cannabis use: comparing GP's and nurses' knowledge, beliefs, and behavior - Norberg Melissa M; Gates Peter; Dillon Paul; Kavanagh David J; Manocha Ramesh; Copeland Jan (BMC, 2012)
Abstract Background General practitioners (GPs) and nurses are ideally placed to address the significant unmet demand for the treatment of cannabis-related problems given the numbers of people who regularly seek their care. The aim of this study was to evaluate differences between GPs and nurses' perceived knowledge, beliefs, and behaviors toward cannabis use and its screening and management. Methods This study involved 161 nurses and 503 GPs who completed a survey distributed via conference satchels to delegates of Healthed seminars focused on topics relevant to women and children's health. Differences between GPs and nurses were analyzed using χ2- tests and two-sample t-tests, while logistic regression examined predictors of service provision. Results GPs were more likely than nurses to have engaged in cannabis-related service provision, but also more frequently reported barriers related to time, interest, and having more important issues to address. Nurses reported less knowledge, skills, and role legitimacy. Perceived screening skills predicted screening and referral to alcohol and other drug (AOD) services, while knowing a regular user increased the likelihood of referrals only. Conclusions Approaches to increase cannabis-related screening and intervention may be improved by involving nurses, and by leveraging the relationship between nurses and doctors, in primary care.